Curriculum ergonomics: Conceptualizing the interactions between curriculum design and use. (2018) - Choppin, Jeffrey; Roth McDuffie, Amy; Drake, Corey; Davis, Jon
Highlights: Curriculum ergonomics helps identify barriers to successful curriculum resource use. The study of curriculum ergonomics highlights influences of curriculum resources. Digital curriculum resources blur the boundaries between design and use. Curriculum resources can be designed to push teachers to new forms of instruction. The study of curriculum ergonomics helps support development of teacher capacity. Abstract: We conceptualize curriculum ergonomics as a field that studies the interactions between users and curriculum materials. We identify five themes that a curriculum ergonomics lens brings into sharper focus: (1) teachers' relationships with and capacity to use curriculum resources; (2) alignment between design intentions and patterns of curriculum use; (3) ways in which curriculum resources influence instruction; (4) ways in which curriculum features are purposefully designed to achieve an educative purpose; and (5) the dissolution of boundaries between design and use. We first summarize the literature in curriculum ergonomics and then show how key themes from that literature inform the discussion of curriculum ergonomics.